CHARACTERISTICS ANALYSIS OF AC-WC MIXTURE WITH POLYVINYL CHLORIDE (PVC) ADDITIONAL INGREDIENTS ON MARSHALL PARAMETERS - Bambang Supriyanto, Tasya Febriana (Universitas Negeri Malang, 2022)
Abstract: PVC waste management is often a problem, and this happens because PVC is a material that cannot be decomposed naturally. Therefore, innovation is needed to dispose of large amounts of PVC waste. One way is to turn the waste into an additive to the asphalt mixture. Adding PVC into asphalt can improve its performance, namely by increasing its softening point value so that asphalt can resist weather changes. This study aims to: (1) Describe the characteristics of the AC-WC mixture without adding PVC in terms of Marshall parameters. (2) describe the characteristics of the AC-WC mixture with the addition of PVC in terms of Marshall parameters. (3) Determine the optimum level of PVC added to the AC-WC pavement mixture. (4) Determine the value of residual strength index (IKS) in the AC-WC mixture with the addition of PVC. PVC material is mixed into the asphalt with variations in the addition of PVC of 0%, 2%, 4%, 6%, 8%, and 10% by weight of the asphalt, and then the Marshall test is carried out. Next, the IKS test specimens were made with optimum bitumen and PVC content, and the Marshall test was carried out. The results of this study showed: (1) The characteristics of the AC-WC mixture without the addition of PVC were that the stability value increased up to 6% and decreased at 6.5% and 7% asphalt content. Meanwhile, the value of flow and VFA has increased. The VIM value decreased, as did the VMA value, which decreased at 5.5% and increased at the next level. (2) The characteristic of the AC-WC mixture with the addition of PVC is that the stability value increases by adding up to 4% PVC content but decreases at 6% to 10%. Flow, VIM, and VMA values increase as the PVC content increases, but VFA values tend to decrease. (3) The optimum level of PVC addition is found at 4.2% by weight of asphalt. (4) The mixture with the addition of 4.2% PVC has a higher IKS value than the mixture without the addition of PVC. This indicates that the AC-WC mixture with the addition of PVC can have better temperature and water resistance compared to the AC-WC mixture without adding additives.Keywords : polyvinyl chloride, asphalt concrete-wearing course, Marshall parameters